Hyperactive MEK1 Signaling in Cortical GABAergic Neurons Promotes Embryonic Parvalbumin Neuron Loss and Defects in Behavioral Inhibition. (11th February 2021) - Holter, Michael C; Hewitt, Lauren T; Nishimura, Kenji J; Knowles, Sara J; Bjorklund, George R; Shah, Shiv; Fry, Noah R; Rees, Katherina P; Gupta, Tanya A; Daniels, Carter W; Li, Guohui; Marsh, Steven; et al.
Abstract: Many developmental syndromes have been linked to genetic mutations that cause abnormal ERK/MAPK activity; however, the neuropathological effects of hyperactive signaling are not fully understood. Here, we examined whether hyperactivation of MEK1 modifies the development of GABAergic cortical interneurons (CINs), a heterogeneous population of inhibitory neurons necessary for cortical function. We show that GABAergic-neuron specific MEK1 hyperactivation in vivo leads to increased cleaved caspase-3 labeling in a subpopulation of immature neurons in the embryonic subpallial mantle zone. Adult mutants displayed a significant loss of parvalbumin (PV), but not somatostatin, expressing CINs and a reduction in perisomatic inhibitory synapses on excitatory neurons. Surviving mutant PV-CINs maintained a typical fast-spiking phenotype but showed signs of decreased intrinsic excitability that coincided with an increased risk of seizure-like phenotypes. In contrast to other mouse models of PV-CIN loss, we discovered a robust increase in the accumulation of perineuronal nets, an extracellular structure thought to restrict plasticity. Indeed, we found that mutants exhibited a significant impairment in the acquisition of behavioral response inhibition capacity. Overall, our data suggest PV-CIN development is particularly sensitive to hyperactive MEK1 signaling, which may underlie certain neurological deficits frequently observed in ERK/MAPK-linked syndromes.